BUDGET POLICY OF HYDROCARBON TRANSPORT ENTERPRISES IN THE FIELD OF DECARBONIZATION - HORAL, Liliana; VOITKIV, Lyudmyla; DUB, Sofiya; STEPANYUK, Olga; YAKUBYSHYN, Oleksandra (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The socio-economic situation of each community, regions and the country as a whole, the implementation of functions and tasks of all authorities, the efficiency of public services and the effectiveness of all participants in the budget process depend on properly organized management of the budget process. The budget process is a continuous process of consistent action aimed at ensuring the sustainable functioning of the budget sector and funding other priority programs and activities.With the implementation of administrative-territorial reform and decentralization of power in Ukraine, the system of inter-budgetary relations and budget equalization in particular has changed. To strengthen the financial base of local budgets, the vector of regulation was shifted from equalization "by expenditure" to equalization "by income". However, the introduction of a new system of financial equalization is associated with a number of risks.Ukraine's oil and gas industry has always been one of the main budget-generators, but the activities of its enterprises are accompanied by the risks of man-made disasters, the consequences of which lead to greenhouse gas emissions. In this article, the authors emphasize the need to form a carbon tax as a compensator for the greenhouse effect and the formation of a quality socially responsible budget policy of enterprises that transport hydrocarbons. A brief overview of the principles and grounds of budget policy of Ukraine. An analysis of carbon pricing initiatives has been made. A list of determinants influencing the decarbonisation process is proposed, and carbon pricing should be based on economic and environmental assessments of man-made risks, as none of the available carbon pricing instruments in the world set the price at a level that would reduce global greenhouse gas emissions.
Keywords: budgeting; carbon tax; decarbonization; long-distance pipelines